Auction‐based competition of hybrid small cells for dropped macrocell users. Issue 6 (1st August 2017) - Basutli, Bokamoso; Lambotharan, Sangarapillai
Abstract : We propose an auction‐based beamforming and user association algorithm for a wireless network consisting of a macrocell and multiple small cell access points (SCAs). The SCAs compete for serving the macrocell base station (MBS) users (MUs). The corresponding user association problem is solved by the proposed bid‐wait auction method. The authors considered two scenarios. In the first scenario, the MBS initially admits the largest possible set of MUs that it can serve simultaneously and then auctions off the remaining MUs to the SCAs, who are willing to admit guest users in addition to their commitments to serve their own host users. This problem is solved by the proposed forward bid‐wait auction. In the second scenario, the MBS aims to offload as many MUs as possible to the SCAs and then admits the largest possible set of remaining MUs. This is solved by the proposed backward bid‐wait auction. The proposed algorithms provide a solution that is very close to the optimum solution obtained by using a centralised global optimisation.